2014
DOI: 10.13087/kosert.2014.17.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Species Distribution Modeling of Endangered Mammals for Ecosystem Services Valuation - Focused on National Ecosystem Survey Data -

Abstract: The provided habitat of many services from natural capital is important. But because most ecosystem services tools qualitatively evaluated biodiversity or habitat quality, this study quantitatively analyzed those aspects using the species distribution model (MaxEnt). This study used location point data of the goat(Naemorhedus caudatus), marten(Martes flavigula), leopard cat(Prionailurus bengalensis), flying squirrel(Pteromys volans aluco) and otter(Lutra lutra) from the 3rd National Ecosystem Survey.Input data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…In our analysis, the AUC values for the yellow-throated marten and leopard cat were 0.810 and 0.645, respectively (Table 4). In the case of leopard cats, it is difficult to exceed 0.7 on average because the occurrence coordinates are widely distributed across the country, similar to general species, and like previous studies that ran MaxEnt models for leopard cats at the national level, we found that the AUC values were relatively low (0.561, 0.629, and 0.761) [25,32,36]. Therefore, although the AUC value does not indicate a very high accuracy, it can be evaluated as relatively reliable because it aligns with relatively low values in previous studies [25].…”
Section: Potential Habitat Analysis Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In our analysis, the AUC values for the yellow-throated marten and leopard cat were 0.810 and 0.645, respectively (Table 4). In the case of leopard cats, it is difficult to exceed 0.7 on average because the occurrence coordinates are widely distributed across the country, similar to general species, and like previous studies that ran MaxEnt models for leopard cats at the national level, we found that the AUC values were relatively low (0.561, 0.629, and 0.761) [25,32,36]. Therefore, although the AUC value does not indicate a very high accuracy, it can be evaluated as relatively reliable because it aligns with relatively low values in previous studies [25].…”
Section: Potential Habitat Analysis Resultssupporting
confidence: 77%
“…The environmental variables used in the MaxEnt model were topography (elevation, gradient, aspect, and topographic wetness), distance (distance from residential areas, used areas, roads, and agricultural land), climate, vegetation (normalized difference vegetation index, diameter, age, and density), and land cover, based on previous studies of yellowthroated martens and leopard cats [6,20,25,[31][32][33][34] (Table 2). The training and test data were selected five times using the cross-validation method.…”
Section: Creating Occurrence Data and Environmental Variablesmentioning
confidence: 99%
“…Species distribution probability was developed based on the third National Ecological Survey data and using the estimated outcomes from Maxent (Jeon et al 2014) based on topography, land cover, and forest type. The point-estimate technique, one of the benefit transfer method was applied for the values for endangered mammal species.…”
Section: Methodsmentioning
confidence: 99%
“…이러한 다양한 성과와 유용성에도 불구하고 공간 자 료의 부족, 모형의 한계, 기후변화 시나리오가 가진 부 정확성 등으로 발생하는 종분포모형의 불확실성은 환 경계획이나 보전계획의 모형 적용에 걸림돌이 되어왔 다 (Flather et al, 1997;Araujo et al, 2005 3_(a)), 이를 sensitivity와 specificity의 합이 최대가 되 는 값을 기준으로 출현/비출현 지도로 변환하였다( Fig. 3_(d)) (Franklin, 2009;Jeon et al, 2014).…”
Section: 서 론 최근 10년간 국외에서는 종분포모형(Speciesunclassified